Advances in semiochemicals of the sweet potato weevil, Cylas formicarius, and its application in pest management - Shuyan He; Chao Li; Yulin Gao (Crop Health, 2026)
Abstract The sweet potato weevil (SPW), Cylas formicarius , is one of the most destructive pests of sweet potato, Ipomoea batatas L., across tropical and subtropical regions worldwide. The concealed feeding habits of larvae and the nocturnal activity of adults render conventional chemical-based control largely ineffective. Semiochemical-based management, especially the use of female-produced sex pheromone, has emerged as a promising strategy for integrated pest management (IPM) for this pest insect. This review provides a comprehensive analysis of the chemical ecology of C. formicarius , including the identification and behavioral activity of the sex pheromone, the diversity and ecological functions of sweet potato plant volatiles, their roles in SPW’s host finding, oviposition, and direct defense, and the development of optimized trapping systems. Applications of the sex pheromone in monitoring, mass trapping, and mating disruption are discussed, together with factors influencing trap efficacy, such as design, color, height, dose, and lure longevity. The integration of pheromone-based tactics with host plant resistance and biological control agents is also addressed. Future research directions for improving the practical use of semiochemicals against this serious pest are proposed.